2021
DOI: 10.1109/tnsre.2021.3096434
|View full text |Cite
|
Sign up to set email alerts
|

Combining Accelerometer and GPS Features to Evaluate Community Mobility in Knee Ankle Foot Orthoses (KAFO) Users

Abstract: Orthotic and assistive devices such as knee ankle foot orthoses (KAFO), come in a variety of forms and fits, with several levels of available features that could help users perform daily activities more naturally. However, objective data on the actual use of these devices outside of the research lab is usually not obtained. Such data could enhance traditional lab-based outcome measures and inform clinical decision-making when prescribing new orthotic and assistive technology. Here, we link data from a GPS unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, combining objective measurement with subjective report may help to understand why capacity often does not relate to performance and how to target this. Ecological momentary assessment, where real-time self-report data are used to provide information on the persons behavior, cognitions, affect, context, and other experiences, 25 could be combined with other technologies including accelerometers and global positioning systems 26,27 to provide a more holistic measure of walking performance.…”
Section: Measuring Walking Recoverymentioning
confidence: 99%
“…Alternatively, combining objective measurement with subjective report may help to understand why capacity often does not relate to performance and how to target this. Ecological momentary assessment, where real-time self-report data are used to provide information on the persons behavior, cognitions, affect, context, and other experiences, 25 could be combined with other technologies including accelerometers and global positioning systems 26,27 to provide a more holistic measure of walking performance.…”
Section: Measuring Walking Recoverymentioning
confidence: 99%
“… 4 A prior study examined orthosis use and community mobility using sensors attached to participants’ orthoses. 5 The authors found that LLO usage and time spent at community locations were not associated with self-reported mobility or performance test outcomes, suggesting that decisions to use LLOs for different activities are not based only upon a user’s mobility level. Further exploration into the situations for which people with LLOs choose to use them could offer insights into how LLO users make decisions to optimize their mobility.…”
Section: Introductionmentioning
confidence: 97%